Designing An Accounting Information System Based On Microsoft Access And Internal Control At Andy’s Taylor - Androni Susanto; Fransiska Fransiska (Universitas Internasional Batam, 2023)
Andy's Taylor is a Limited Liability Company engaged in sewing various types of clothing located in Komp. Bukit Beruntunng Blok D No 7. Andy's Taylor provides tailoring services in the form of clothes that are used for everyday life such as clothes, pants, skirts, dresses. In addition, there are also sewing blankets, pillowcases, bedcover towels, etc. The problem found is that in carrying out its business activities, Andy's Taylor does not carry out systematic accounting records to record every transaction that occurs. Lack of recording can lead to inaccurate decision making because business owners do not clearly know the financial flow of the business. So that the solution that can be given to Andy's Taylor is to design an accounting record system using Microsoft Access. The design of this system is made simply so that the owner can use this system easily and help the owner to monitor every activity related to operations and also so that the owner can make decisions for the future by analyzing the financial statements generated from this system. The design of this system will provide recording forms for cash disbursements, cash receipts, and inventory transactions. The result of the implementation of this PKM project is to produce a complete and accurate financial report consisting of a statement of financial position, income statement, statement of changes in equity